Identification of Intestinal Helminths in Cockroaches found in Selected Public Market of Davao City - Martinez, Paolo D.; Adlaon, Katherine T.; Silguera, Junelle P. (Future Science / FSH-PH Publications, 2024)
Cockroaches are resilient insects that thrive in various environments, including public markets. These creatures can act as mechanical vectors for intestinal helminths, posing a risk to human health. This study aimed to identify and measure the infestation rate of intestinal helminths in cockroaches from Bankerohan Public Market and Agdao Public Market in Davao City. Cockroaches were collected using specialized traps via the “catch-and-release” method, and the presence of intestinal parasites on their external surfaces was determined. The study found that cockroaches from both markets harbored Hookworm and Ascaris lumbricoides, with Ascaris lumbricoides having the highest frequency and infestation rate among the entire population of cockroaches gathered from both markets. The infestation rate of Ascaris lumbricoides was higher in the Bankerohan public market compared to the Agdao public market; however, the findings reveal that there is no correlation between the frequency of the parasites and the public market studied, indicating that the occurrence of the parasites cannot be attributed to the location of the public markets. The study highlights the need for improved sanitation practices and awareness to control parasite transmission through cockroaches, which can serve as vectors for these pathogens.